MODEL OF MAXIMUM STRESS IN THE TERMAL-CYCLE TESTS ON THE DURABILITY OF HEATPROOF MATERIALS - Кулик, М.; Кучер, О.; Дубровський, C.; Петрук, Я.; Ковешніков, М. (Science-based technologies, 2010)
The considered resource possibilities of heatproof materials of rotor details of "hot part" of aviation turboengines(GTE) and power plants (PP) are in speed-up thermal-cycle tests. The shown possibility of applicationof calculation method is on the basis of empiric mathematical model of maximum thermo-mechanical tensions ofextreme levels which operate in the critical points of details of "hot part" of GTE. It is thus assumed that thestandards of materials work on the thermal-cycle modes of maximally close to the terms of work of rotor detailsin critical points which limit tenure of employment and appointed resource of aviation GTE and PP.